Structural, thermal and optical properties of rare earth doped lead-tellurite oxide glasses - Lim, Fong Peng; Omar Baki, Sharudin; Arifin, N. M.; Mansor, Yaakob; Nazri, Ahmad; Abbas, Bashar Khudhair (Akademia Baru Publishing, 2021)
Structural, thermal and optical properties of lead-tellurite oxide glasses consisting TeO2 – PbO – Bi2O3 – Er2O3, synthesized by high temperature melt-quenching-thermal annealing method were investigated in this study. The role of rare-earth element, erbium ion as dopant into the host glass has affected physically, thermally and optically of the glasses. The amorphous nature of the glasses was confirmed by XRD (x-ray diffraction). Thermal exo-endothermic event profiles clarify its glass transformation temperature Tg, crystallization temperature Tx, and melting temperature Tm are exist. Both UV-Vis-NIR optical absorption and Raman spectroscopy have revealed optical energy gap changes due to the structural deformation by the erbium ions. Related obtained glass parameters such as polarizability, refractive indices and metallization criterion were also explained further in this study.